ACCEPTANCE OF ISLAMIC EQUITY-BASED MORTGAGE PRODUCT: AN EXTENSION OF DECOMPOSED THEORY OF PLANNED BEHAVIOUR - Shaikh, Imran Mehboob; Noordin, Kamaruzaman (Journal of Islamic Monetary Economics and Finance, 2020)
This study examine the determinants that may predict the consumer’s intention to accept equity-based product, which is mushārakah mutanāqisah (MM) Islamic mortgage. Survey was conducted using multi-stage and purposive sampling. For the purpose of analysis structural equation modelling technique was used in current research. Moreover, 306 responses were gathered from users of MM Islamic mortgage. The theoretical framework of the current study was drawn upon the decomposed theory of planned behaviour (DTPB) because of its predictive power and robustness to base a model. The findings of the study revealed that behavioural intention appeared to have been directly and indirectly influenced by all constructs and above all most significant factors are Peers and perceived behaviour control. All the main beliefs, namely, attitude, subjective norm, perceived behaviour control, which are predicted by compatibility, relative advantage, peers and self-efficacy affects consumers’ intention to accept mushārakah mutanāqisah, MM home financing. The effect of pricing variable on intention was significant as well. Pricing variable is yet to be tested therefore, this paper will be a useful reference for the policymakers, academicians and future researchers.